Determination of The Best Koperasi Using SAW (Simple Additive Weighting) - Ines Saraswati Machfiroh; Widiya Astuti Alam Sur; Jaka Permadi; Winda Aprianti; Herfia Rhomadhona (Eigen Mathematics Journal, 2023)
Office of Koperasi, UKM, and Trade of Tanah Laut Regency, South Kalimantan conducts the health of Koperasi by manually checking the financial report data of each Koperasi. This study aims to determine the best Koperasi performance using a decision-making system with the Simple Additive Weighting (SAW) method. Performance evaluation is based on the criteria in the Technical Instructions for the Deputy for Koperasi Number 15 of 2021 concerning Guidelines for Working Papers on Cooperative Health Examination. The criteria to determine the best Koperasi performance were based on the attributes of the governance, risk profile, financial performance, and capital of Koperasi. The SAW method was used to select the best Koperasi by adding up each attribute, then multiplying by the weight of the related attributes. Based on the calculations using the SAW method, Koperasi 33 was selected, with the highest Vector value (V(i)) of 0.944719. Koperasi 33 can be categorized as the best of 100 Koperasi in Tanah Laut Regency, South Kalimantan.